The Importance of Shariah Compliance Disclosure in Malaysian Islamic Financial Institutions: Accountability of the Shariah Committee Members - Nur Laili Ab Ghani; Noraini Mohd Ariffin; Abdul Rahim Abdul Rahman (Universiti Sains Islam Malaysian, 2024)
Page : 2-4